KOMUNITAS PASIEN KANKER (STUDI MENGENAI PEMBENTUKAN KOMUNITAS PADA PASIEN KANKER PAYUDARA DI INSTALASI KANKER TERPADU TULIP RSUP DR SARDJITO DAERAH ISTIMEWA YOGYAKARTA) - , Ratna Dewi, S.Sos. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The contrast in the services and facilities of health sector inter-regionally has become one of the matters encouring people to move to find far more complete health facilities. This research was aimed to determine the process of the decision-making of the cancer patient for treatment in Yogyakarta. This happened due to the limited cancer facilities and services in a nymber of hospitals. In addition, it was to determine the formation of community among cancer patient in Tulip Integrated Cancer Installation in Dr. Sardjito General Central Hospital, Yogyakarta The research used descriptive qualitative method. The research was conducted from June t August 2008, in Dr. Sardjito Central General Hospital, Yogyakarta, on the basis that the hospital provided special services and facilities for people with cancer i.e. âTulip Integrated Cancer Installationâ. The informant selection technique was conducted using purposive technique. Considering the large number of cancer patient, the selection of the informants was conducted by sorting out the research subject into categories corresponding to the needs of the research. The data collection method was done by in depth interviews which were guided by interview guidelines, observations and secondary data. The data analysis technique used in this research was qualitative analysis and the analisys model used was interactive analysis. The result of the research shows that the limitation of health care facilities in the native region is one of the matters causing the patients to take medication outside their domicilies. Although the decision is not easy to be taken due to issues related to the family or the work which must be abandoned. The intensity of the inter-patientsâencounter in the environment of Tulip Integrated Cancer Installation is relatively regular due to the routines of the therapy schedule, therefore, it creates a sense of closeness and a sense of common faith of being in the same boat which emerge among the fellow cancer patients. This creates togetherness, and a community emerges among the fellow cancer patients, either among themselves, among the patiens with the medical personnel, among the patients with the other patientsâfamilies and among the patientsâ families.